STATE SUPPORT OF AGROINDUSTRIAL COMPLEX SOME LEGAL ISSUES (Journal of actual problems of jurisprudence, 2019)
In 2003-2005, the state declared the year of agriculture.No. But, despite the fact that in these years he worked hard, big issues in achieving results1). In addition, this year our country conducted the census" agriculture".. "Amnesties" at the beginning of the process can not but please the public. But agree with those,there are enough unsolved problems in the village. How to solve? Before resolving the issue hehow to answer the question, where did the question. Because Kazakhstan will join the WTOentering the number of States that with modern competitive agriculture intalyrequirement. Therefore, this issue is directly related to the sphere of agriculture and agriculture.the lands of the territories are under its jurisdiction.